2015
DOI: 10.1016/j.nut.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Stress and dietary behaviour among first-year university students in Australia: Sex differences

Abstract: These results demonstrate a clear difference in food selection patterns between stressed male and female students, with stress being a more significant predictor of unhealthy food selection among male students. Further research is needed using a qualitative approach to understand how stress and eating behavior are related in university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 35 publications
12
93
2
9
Order By: Relevance
“…As suggested by Papier et al (2015), the results show that 52.9% of participating students felt distressed and that both girls and boys consumed larger quantities of 'unhealthy' food (with higher fat and sugar) as a result. The preventive measure recommended to university students is an active lifestyle, the importance of which is acknowledged by most students; they are also aware of relevant health risks (consequences of smoking, alcohol, poor dietary habits and lack of physical activity).…”
Section: Lifestyle In University Studentsmentioning
confidence: 60%
“…As suggested by Papier et al (2015), the results show that 52.9% of participating students felt distressed and that both girls and boys consumed larger quantities of 'unhealthy' food (with higher fat and sugar) as a result. The preventive measure recommended to university students is an active lifestyle, the importance of which is acknowledged by most students; they are also aware of relevant health risks (consequences of smoking, alcohol, poor dietary habits and lack of physical activity).…”
Section: Lifestyle In University Studentsmentioning
confidence: 60%
“…Conversely, the association has also been observed in the opposite direction, that is, stress has been found to be associated with poor food selection [12][13][14], but results are not always consistent [15,16]. In a recent study, we demonstrated that stress was associated with unhealthy food selection among university students, with stress being a more significant predictor of unhealthy food selection among male students [17]. Others have also shown that inadequate nutrition and poor diet quality were likely to be directly associated with mental health problems [10][11].…”
Section: Introductionmentioning
confidence: 83%
“…In light of the rapid rise in mental health problem in young adults, an increasing body of literature has sought to examine prevalence of stress among university students [2][3][6][7]17,[24][25].Building on the previous studies, the present study focused on identifying the potential risk factors of stress among undergraduate university students attending an Australian University. This study found that sex, marital status, academic group, weekly working hours, frequency of exercise, overweight/obesity and dietary patterns were significant predictors of different levels of stress and thus indicating a complex relationship of various socio-demographic, health and behavioural factors with stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Psychological distress among university students has frequently been associated with stress, which is also common among university students and more so for females than males. [13][14][15][16] Students have been found to be mostly worried about how they achieve in their academic studies, the stress of being successful in their studies and future plans post education. Further, psychological distress has been related to financial concerns and interpersonal relationships among university students.…”
Section: The Problemmentioning
confidence: 99%